PENGEMBANGANAPLIKASI REPOSITORY PORTOFOLIO DOSEN DAN STAFF MIPOLINEMA DENGAN METODE N-TIER - Andoko, Banni Satria (DINAMIKA DOTCOM, 2015)
Object oriented application had been developed by many ways, one of the famous ways is N-Tier concept. By using it, the class had been devided into three parts. There are : model, logic and data.Model unit is the attribut part, logic and data is the method part. The diffrent between logic and data is the data tier communicate directly into database. and the other tier is presentation tier.Â  By seperating each layer, the application become easy to maintain and the every change of the layer will never impact other layer. Based on the encapsulation concept on object oriented programing. To meet the need of relational data, the application use the ORM concept. By using ORM the SQL query will never had a join query. And every class will represent for every table in the database. Keyword:ORM, N-Tier, .Net, OOP